2021
DOI: 10.1016/j.ijid.2021.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Non-Polio Enteroviruses recognized in the framework of the Acute Flaccid Paralyses (AFP) surveillance system in Northern Italy, 2016–2018

Abstract: Background: Acute Flaccid Paralyses Surveillance (AFPS) monitors the emergence of polioviruses and can track Non-Polio Enteroviruses (NPEVs). We report AFPS activity in the Lombardy region (Northern Italy) from 2016 to 2018. Methods: Fecal and respiratory samples were collected from children <15 years who met the WHO definition of an AFP case, analyzed by virus isolation in cell cultures (RD/L20B) and by a one-step realtime RT-PCR assay specific for the 5 0 -noncoding-region of NPEV. NPEV-positive specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Thus, the frequency of NPEV isolation from stool samples allows the assessment of the quality of surveillance for poliomyelitis and AFP. The frequency fluctuates in different countries depending on climatic and socio-economic conditions [14][15][16][17]. According to our data, in the Russian Federation, the proportion of AFP cases positive for NPEV was 3.2% in the period 2000-2019 (238 out of 7414).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the frequency of NPEV isolation from stool samples allows the assessment of the quality of surveillance for poliomyelitis and AFP. The frequency fluctuates in different countries depending on climatic and socio-economic conditions [14][15][16][17]. According to our data, in the Russian Federation, the proportion of AFP cases positive for NPEV was 3.2% in the period 2000-2019 (238 out of 7414).…”
Section: Discussionmentioning
confidence: 62%
“…The proportion of AFP cases from which non-polio enteroviruses (NPEV) were isolated varies from country to country: 4.3% in Tunisia [14], 6.12% in Poland [15], 19.4% in Italy [16], and 20.8% in the Philippines [17]. The etiological role of NPEV is not always obvious, since the WHO-recommended AFP case investigation algorithm consists of examining stool samples [18], and the isolation of ubiquitously present NPEV from a non-sterile specimen may be an accidental finding.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that non‐polio enterovirus (NPEV) infections are not notifiable infectious diseases in Italy, the circulation of E11 in Lombardy (Northern Italy), where the first two cases of E11 neonatal infection were reported, has been implemented in the period April‐December 2023. In detail, an event‐based surveillance and a hospital‐based surveillance considering inpatients exhibiting respiratory or neurological symptoms have showed a total of 20 additional cases 6 . Recently, a wastewater‐based surveillance (WBS) performed in Sicily (a region in Southern Italy) between June 2022 and June 2023, showed that the new E11 lineage has circulated in this region during early 2023 7 .…”
Section: Introductionmentioning
confidence: 99%
“…These new diagnostic possibilities have identified new or old members belonging to EV A–D or RV A–C like viruses that engender the common cold. In addition, sequencing of partial genomes of the virus in samples from large patient cohorts with various diseases has resulted in increased knowledge of the clinical impact of different EV types 10–12 . Thus, EV‐D68, which was previously considered a virus causing mild upper respiratory disease, has recently been shown to cause large outbreaks of more severe disease with complications such as acute flaccid myelitis 4,13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sequencing of partial genomes of the virus in samples from large patient cohorts with various diseases has resulted in increased knowledge of the clinical impact of different EV types. [10][11][12] Thus, EV-D68, which was previously considered a virus causing mild upper respiratory disease, has recently been shown to cause large outbreaks of more severe disease with complications such as acute flaccid myelitis. 4,[13][14][15] Likewise, members belonging to species RV C have been shown to cause more severe upper and lower respiratory diseases than those belonging to RV types A or B.…”
mentioning
confidence: 99%